Modified Nanoporous Asymmetric Polyacrylonitrile Membranes with Merpol as a Hydrophilic Surfactant: Insulin Separation - Agarwal, Shilpi; Tyagi, Inderjeet; Gupta, Vinod Kumar (Asian Journal of Chemistry, 2016)
Polyacrylonitrile (PAN) membranes are broadly applied in many chemical engineering fields. In this research, asymmetric polyacrylonitrile membranes with high hydrophilicity and permeability were prepared from PAN/merpol/NMP system via immersion precipitation. Pure water was used as gelatin media. The effect of variation of polyacrylonitrile molecular weight and addition of merpol on morphology, wet ability, pure water permeation flux and insulin rejection of the prepared membranes were studied by scanning electron microscopy, contact angle measuring instrument and experimental set up. The results demonstrated that both hydrophilicity and permeability of the prepared membranes were significantly enhanced by small additions of merpol surfactant in the casting solution. It was also found out that decrease in the polyacrylonitrile molecular weight results in the formation of membranes with high permeability and sub-layer porosity.